An alternative interpretation of cellular 'selfish spermatogonial selection'‐ clusters in the human testis indicates the need for 3‐D‐analyses. (19th February 2016) - Pohl, E.; Gromoll, J.; Kliesch, S.; Wistuba, J.
Summary: The 'selfish spermatogonial selection'‐ model was proposed to explain the paternal age effect (PAE) of some congenital disorders associated with point mutations in male germ cells. According to this, spermatogonia carrying pathogenic mutations gain a selection advantage over non‐mutated spermatogonia which leads to an increased number of mutated spermatogonia and consequently spermatozoa over time. Recently, an immunohistochemical approach using the premeiotic marker melanoma antigen family A4 (MAGE A4) was undertaken by the Wilkie group to confirm the presence of microclones of putatively mutated spermatogonia in testes of elderly men. The objective of our study was the age‐dependent assessment of testes from men with normal spermatogenesis using MAGE A4 immunohistochemistry to identify and corroborate cellular clusters indicative for 'selfish spermatogonial selection' in our cohort. We analyzed testicular tissues obtained from men with normal spermatogenesis assigned to three age groups [(1) 28.8 ± 2.7 years; (2) 48.1 ± 1 years; (3) 71.9 ± 6.8 years, n /group = 8]. We could detect very similar distribution patterns of MAGE A4‐positive cells and the presence of several types of microclusters as reported previously. However, these cellular clusters, indicative for clonal expansion, were not only present in testes from elderly men but also in those from age group 1 and 2. Using graphical three‐dimensional modelling, we identified that cross‐section directions e.g . longitudinal sections might provoke misleading interpretation of spermatogonial clusters, in particular when the tissue processing is limited. Thus, appropriate fixation and embedding is needed for reliable analysis of testicular sections. We therefore propose a more careful interpretation of such spermatogonial clusters and recommend a 3‐D analysis to unequivocally determine 'selfish spermatogonial selection'‐manifestations.